Is Platelet-rich Plasma Injection Effective for Chronic Achilles Tendinopathy? A Meta-analysis. Issue 8 (August 2018) - Zhang, Yi-Jun; Xu, San-Zhong; Gu, Peng-Cheng; Du, Jing-Yu; Cai, You-Zhi; Zhang, Chi; Lin, Xiang-Jin
Abstract: Background: Chronic Achilles tendinopathy is common in the general population, and platelet-rich plasma (PRP) is seeing increased use to treat this problem. However, studies disagree as to whether PRP confers a beneficial effect for chronic Achilles tendinopathy, and no one to our knowledge has pooled the available randomized trials in a formal meta-analysis to try to reconcile those differences. Questions/purposes: In the setting of a systematic review and meta-analysis of randomized controlled trials (RCTs), we asked: Does PRP plus eccentric strength training result in (1) greater improvements in Victorian Institute of Sports Assessment-Achilles (VISA-A) scores; (2) differences in tendon thickness; or (3) differences in color Doppler activity compared with placebo (saline) injections plus eccentric strength training in patients with chronic Achilles tendinopathy? Methods: A search of peer-reviewed articles was conducted to identify all RCTs using PRP injection with eccentric training for chronic Achilles tendinopathy in the electronic databases of PubMed, Web of Science (SCI-E/SSCI/A&HCI), and EMBASE from January 1981 to August 2017. Results were limited to human RCTs and published in all languages. Two reviewers assessed study quality using the Cochrane Collaboration risk-of-bias tool. All the included studies had low risk of bias. The primary endpoint was improvement in the VISA-A score, which ranges from 0 to 100 points, with higher scores representing increased activity and less pain; we considered the minimum clinically important difference on the VISA-A to be 12 points. Secondary outcomes were tendon thickness change (with a thicker tendon representing more severe disease), color Doppler activity (with more activity representing a poorer result), and other functional measures (such as pain and return to sports activity). Four RCTs involving 170 participants were eligible and included 85 participants treated with PRP injection and eccentric training and 85 treated with saline injection and eccentric training. The patients in both PRP and placebo (saline) groups seemed comparable at baseline. We assessed for publication bias using a funnel plot and saw no evidence of publication bias. Based on previous studies, we had 80% power to detect a 12-point difference on the VISA-A score with the available sample size in each group. Results: With the numbers available, there was no difference between the PRP and saline groups regarding the primary outcome (VISA-A score: mean difference [MD], 5.3; 95% confidence interval [CI], -0.7 to 11.3; p = 0.085). Likewise, we found no difference between the PRP and saline groups in terms of our secondary outcomes of tendon thickness change (MD, 0.2 mm; 95% CI, 0.6-1.0 mm; p = 0.663) and color Doppler activity (MD, 0.1; 95% CI, -0.7 to 0.4; p = 0.695). Conclusions: PRP injection with eccentric training did not improve VISA-A scores, reduce tendon thickness, or reduce color Doppler activity in patients with chronic Achilles tendinopathy compared with saline injection. Larger randomized trials are needed to confirm these results, but until or unless a clear benefit has been demonstrated in favor of the new treatment, we cannot recommend it for general use. Level of Evidence: Level I, therapeutic study.